Artificial nail composition

Optimizing the spacer group length and acrylate composition in artificial nail compositions addresses hydrolysis and separation issues, maintaining adhesion and durability in high-temperature and humid environments, ensuring stable performance and safety.

JP2025016844AActive Publication Date: 2025-02-05CONFESTA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023119582
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-02-05
Estimated Expiration
2043-07-24

AI Technical Summary

Technical Problem

Existing artificial nail compositions face issues with hydrolysis and separation of components due to exposure to high-temperature and humid environments, leading to reduced adhesion, durability, and stability, especially in summer conditions, which can cause health risks and affect the adhesive properties.

Method used

Incorporating a specific structure with a spacer group between the hydrophilic phosphate group and hydrophobic polymerization group, where the chain length of the spacer group is optimized to maintain compatibility and balance, using acrylate compounds with hydroxyl groups, and controlling the content of hydrophilic compounds to prevent separation and improve adhesion.

Benefits of technology

The solution provides stable artificial nail compositions that maintain adhesion and durability even in high-temperature and humid conditions, preventing hydrolysis and separation, ensuring long-term adhesive performance and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016844000001
    Figure 2025016844000001
  • Figure 2025016844000002
    Figure 2025016844000002
  • Figure 2025016844000003
    Figure 2025016844000003
Patent Text Reader

Abstract

To provide an artificial nail composition that suppresses the hydrolysis of compounds exemplified by urethane acrylate and (meth)acrylate monomers, which results from exposure to high-temperature or high-humidity environments, specifically, the degradation of phosphate group-containing polymerizable monomers resulting from an imbalance in their mutual compatibility.SOLUTION: An artificial nail composition comprises (A) a compound having at least one radical-polymerizable unsaturated double bond in each molecule, free of phosphorus atoms, (B) an acidic phosphorus compound having at least one radical-polymerizable unsaturated double bond in each molecule, and (C) a radical polymerization initiator. The component (B) comprises at least one selected from hydroxybutyl (meth)acrylate acid phosphate, hydroxypentyl (meth)acrylate acid phosphate, and hydroxyhexyl (meth)acrylate acid phosphate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to artificial nail compositions. [Background technology]

[0002] A polymer obtained by copolymerizing a compound having a radically polymerizable unsaturated bond with another copolymerizable monomer has film-forming properties and is used as an artificial nail composition.

[0003] Properties required for an artificial nail composition include adhesion between the natural nail and the artificial nail, surface smoothness and gloss, and film durability, and for example, an artificial nail composition has been proposed that contains (a) a compound having at least one radically polymerizable unsaturated double bond in the molecule, (b) an acidic phosphorus compound having a specific methacrylate group, and (c) a radical polymerization initiator (see Patent Document 1). The compound described in Patent Document 1 makes it possible to provide an artificial nail composition that satisfies these properties. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 7104392 Summary of the Invention [Problem to be solved by the invention]

[0005] When using the artificial nail composition, the lid is left open and the composition is taken out with a brush or the like, and then applied to the nail. Therefore, the composition is exposed to the outside air for a long period of time during the application, and moisture absorption into the artificial nail composition is observed during the hot and humid summer months. This moisture absorption causes hydrolysis of compounds such as urethane acrylate and (meth)acrylate monomer, which may result in a decrease in viscosity of the artificial nail composition and the generation of an unpleasant odor.

[0006] In addition, since the artificial nail composition is shipped to the general market as a mixture of (meth)acrylate oligomer and monomer before hardening and provided to users via an intermediary, it is impossible to control the storage environment of the artificial nail composition. Therefore, it may be stored for a long time in a high temperature environment, and even in a sealed container, hydrolysis and hardening (gelation) of the raw materials, and the associated separation, precipitation, and changes in properties may be observed.

[0007] The compound described in Patent Document 1 contains an acidic phosphorus compound. The hydrolysis of compounds such as urethane acrylate and (meth)acrylate monomers is accelerated in an acidic environment, and therefore, a significant change may occur in a system containing an acidic phosphorus compound. In the promotion of hydrolysis, low molecular weight compounds are generated, which may cause health hazards, such as skin irritation and sensitization due to low molecular weight, and therefore, changes in properties in high temperature and high humidity environments must be avoided.

[0008] In addition, the artificial nail composition is a mixture of compounds having a (meth)acrylate group, and may gel in a high temperature or high humidity environment. In particular, in a high temperature and high humidity environment, gelation may occur due to a chemical curing reaction of the content components, and the composition may become unusable. The phosphate group-containing polymerizable monomer corresponding to component (b) has a lower reactivity than a polymerizable monomer that does not contain a phosphate group, so it also functions as a stabilizer for the entire artificial nail composition, and when each component contained in the artificial nail composition is uniformly dispersed, it is stable even in a high temperature environment. However, the compatibility of the phosphate group-containing polymerizable monomer with the main component system of the artificial nail composition may decrease, and when the compatibility decreases, the phosphate group-containing polymerizable monomer may change (separation, precipitation, sedimentation), and at the same time, gelation of the artificial nail composition may be observed, and the adhesiveness to the nail may decrease. Furthermore, the strength of the cured product may change due to the change (separation, precipitation, precipitation), and in many cases, the product may become brittle or soft. As a result, it may not be possible to maintain adhesiveness for a long period of time.

[0009] This causes a significant decrease in the functionality of the artificial nail composition. In artificial nail compositions, which are mixtures of hydrophobic and hydrophilic compounds, there is a daily demand for improvements to suppress separation, precipitation, sedimentation, etc. of specific components, which is one of the market demands.

[0010] An object of the present invention is to provide an artificial nail composition which suppresses hydrolysis of compounds such as urethane acrylates and (meth)acrylate monomers caused by exposure to a high temperature or high humidity environment, in particular, deterioration of the phosphate group-containing polymerizable monomer caused by loss of balance in the compatibility of the phosphate group-containing polymerizable monomer. [Means for solving the problem]

[0011] The phosphate group-containing polymerizable monomer has a structure in which a spacer group exists between a hydrophilic phosphate group and a hydrophobic polymerizable group. The present inventors have focused on the spacer group and found that when the spacer group has a specific length, the phosphate group-containing polymerizable monomer as a whole has an excellent balance of hydrophilicity and hydrophobicity, and can maintain compatibility with the artificial nail composition even in a high temperature or high humidity environment, and have completed the present invention. Specifically, the present invention provides the following.

[0012] A first aspect of the invention provides an artificial nail composition comprising: (A) a compound having at least one radically polymerizable unsaturated double bond in the molecule and having no phosphorus atom; (B) an acidic phosphorus compound having at least one radically polymerizable unsaturated double bond in the molecule; and (C) a radical polymerization initiator, wherein the component (B) includes one or more selected from hydroxybutyl (meth)acrylate acid phosphate, hydroxypentyl (meth)acrylate acid phosphate, and hydroxyhexyl (meth)acrylate acid phosphate.

[0013] According to the first feature of the invention, the chain length of the spacer group of the acidic phosphorus compound, which is component (B), is within the range of C4 (number of carbon atoms: 4) to C6 (number of carbon atoms: 6), and an artificial nail composition can be provided that suppresses separation, precipitation, sedimentation, etc. of specific components even in high temperature and humid environments. Specifically, an artificial nail composition can be provided that suppresses hydrolysis of components (A) and (B) caused by being placed in a high temperature and humid environment, and in particular, deterioration of the phosphate group-containing polymerizable monomer caused by a loss of balance in the compatibility of the phosphate group-containing polymerizable monomer. This makes it possible to provide an artificial nail composition that can be stably applied even in the hot and humid summer season.

[0014] If the chain length of the spacer group is insufficient, the phosphatic / phobic balance of the entire phosphate group-containing polymerizable monomer is biased toward hydrophilicity, and when the artificial nail composition is placed in a high-temperature or humid environment, the phosphate group-containing polymerizable monomer separates, affecting adhesion and curing properties. Also, if the chain length of the spacer group is too long, the phosphatic / phobic balance of the entire phosphate group-containing polymerizable monomer is biased toward hydrophobicity, and when the artificial nail composition is placed in a high-temperature or humid environment, the adhesive function of the phosphate group, which is a hydrophilic group, is significantly reduced, affecting adhesion.

[0015] A second feature of the invention is the first feature of the invention, which provides an artificial nail composition, wherein the component (A) contains a (meth)acrylate that does not have a hydroxyl group and a (meth)acrylate that has a hydroxyl group.

[0016] According to the second aspect of the invention, the affinity-inhibition balance of the composition can be more appropriately maintained.

[0017] A third aspect of the invention is the second aspect of the invention, wherein the (meth)acrylate having a hydroxyl group includes hydroxyethyl (meth)acrylate and / or hydroxypropyl (meth)acrylate.

[0018] According to the third feature of the invention, in component (A), the spacer group present between the hydrophilic hydroxyl group and the hydrophobic polymerizable group has 2 or 3 carbon atoms. Since component (A) as well as component (B) have an excellent balance of hydrophilicity, the compatibility of the artificial nail composition can be maintained more appropriately even in high temperature or high humidity environments.

[0019] A fourth feature of the invention is the second or third feature of the invention, providing an artificial nail composition in which the content of the (meth)acrylate having a hydroxyl group is 35 parts by mass or less per 100 parts by mass of the artificial nail composition.

[0020] Although the hydrophilic compound is expected to have a certain effect in suppressing the clouding of the cured product over time, a high ratio of the hydrophilic compound may affect the strength of the cured product. In addition, a high ratio of the hydrophilic compound may cause problems due to absorption of moisture from the natural nail. According to the fourth feature of the invention, since the content of the (meth)acrylate having a hydroxyl group is within a predetermined range, it is possible to provide an artificial nail composition that has sufficient strength of the cured product and is capable of suppressing the clouding of the cured product over time. In addition, it is possible to prevent problems due to absorption of moisture from the natural nail. Effect of the Invention

[0021] According to the present invention, an artificial nail composition can be provided that suppresses hydrolysis of compounds such as urethane acrylates and (meth)acrylate monomers caused by exposure to high temperature or high humidity environments, and in particular, the deterioration of the phosphate group-containing polymerizable monomer caused by loss of the compatibility balance of the phosphate group-containing polymerizable monomer, thereby providing an artificial nail composition that can be stably applied even in the hot and humid summer season. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, an example of a preferred embodiment of the present invention will be described with reference to the drawings. Note that this is merely an example, and the technical scope of the present invention is not limited to this example.

[0023] <Artificial nail composition> The artificial nail composition according to this embodiment contains component (A): a compound having at least one radically polymerizable unsaturated double bond in its molecule, component (B): an acidic phosphorus compound having at least one radically polymerizable unsaturated double bond in its molecule, and component (C): a radical polymerization initiator.

[0024] [Component (A): a compound having at least one radically polymerizable unsaturated double bond in the molecule and having no phosphorus atom] The type of component (A) is not particularly limited, but in order to maintain the balance of the affinity and affinity of the composition even after it is placed in a high-temperature or high-humidity environment, it is preferable that component (A) contains a (meth)acrylate that does not have a hydroxyl group and a (meth)acrylate that has a hydroxyl group.

[0025] Examples of (meth)acrylates that do not have a hydroxyl group include monofunctional monomers such as alkyl (meth)acrylates, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, amyl (meth)acrylate, hexyl (meth)acrylate, and heptyl (meth)acrylate, (meth)acrylates of alkylene oxide adducts of alkylphenols, cyclohexyl (meth)acrylate, and benzyl (meth)acrylate.

[0026] Examples of the difunctional or higher functional monomer include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, and butylene glycol di(meth)acrylate.

[0027] Examples of the (meth)acrylate of an alkylene oxide of a polyol include tetramethylolmethane tetra(meth)acrylate, trimethylolethane tri(meth)acrylate, ditrimethylolethane tritetra(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, glyceryl tri(meth)acrylate, diglycerin tetra(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0028] Further examples include di(meth)acrylates of alkylene oxide modified bisphenols such as bisphenol A, F, S, etc., di(meth)acrylates of hydrogenated bisphenols such as bisphenol A, F, S, etc., di(meth)acrylates of alkylene oxide modified hydrogenated bisphenols such as bisphenol A, F, S, etc., and di(meth)acrylates of alkylene oxide modified trisphenols.

[0029] Another example is isobornyl(meth)acrylate, in which a (meth)acrylic group is bonded to an isobornyl group (one OH group removed from isobornyl).

[0030] Among them, the (A) component preferably contains an alkyl (meth)acrylate monomer and / or an isobornyl (meth)acrylate monomer, and more preferably contains an alkyl methacrylate monomer and / or an isobornyl methacrylate monomer, which allows the formation of an artificial nail having superior hardness.

[0031] Examples of the (meth)acrylate having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 3-chloro-2-hydroxypropyl (meth)acrylate.

[0032] Further examples include polyfunctional monomers such as polylactonate di(meth)acrylates of alkylene glycols such as polyethylene glycol and polypropylene glycol, and polylactonate (meth)acrylates of glycerin, diglycerin, trimethylolpropane, ditrimethylolpropane, pentaerythritol, dipentaerythritol, and the like.

[0033] Among these, in order to maintain the balance of the affinity and affinity of the component (A) even after it is placed in a high temperature or humid environment, it is preferable that the spacer group between the hydrophilic hydroxyl group and the hydrophobic polymerizable group has a chain length within the range of C2 (number of carbon atoms: 2) to C3 (number of carbon atoms: 3). Examples of (meth)acrylates having a hydroxyl group and having a spacer group chain length within the range of C2 to C3 include 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate.

[0034] In this embodiment, the term "(meth)acrylate" means either acrylate or methacrylate. (Meth)acrylate is a general term for acrylate and methacrylate, and includes both acryloyl group-containing polymerizable monomers and methacryloyl group-containing polymerizable monomers.

[0035] The component (A) may be a mixture of two or more kinds, rather than one kind. The artificial nail composition may also contain, in addition to the component (A), other polymerizable compounds, such as oligomers or polymers of monomers having at least one or more polymerizable groups in the molecule. The component (A) may also have a substituent such as an acidic group or a fluoro group in the same molecule.

[0036] An example of an oligomer having multiple (meth)acryloyl groups in a molecule is a (meth)acrylate oligomer having a molecular chain structure formed by polymerizing multiple monomers and multiple (meth)acryloyl groups in a molecule. The weight average molecular weight of the (meth)acrylate oligomer is usually 400 or more and 50,000 or less.

[0037] Examples of the (meth)acrylate oligomer include a urethane (meth)acrylate oligomer having a plurality of urethane bonds in the molecular chain, an epoxy (meth)acrylate oligomer having a molecular chain generated by a ring-opening reaction of an epoxide, a polyester (meth)acrylate oligomer having a plurality of ester bonds in the molecular chain, and a polyether (meth)acrylate oligomer having a plurality of ether bonds in the molecular chain.

[0038] The mass ratio of the (meth)acrylate without a hydroxyl group (hydrophobic polymerizable monomer) and the (meth)acrylate with a hydroxyl group (hydrophilic polymerizable monomer) is not particularly limited, but in order to maintain the balance of the hydrophilicity of the (A) component, the upper limit of the content of the (meth)acrylate with a hydroxyl group is preferably 35 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 25 parts by mass or less, and particularly preferably 20 parts by mass or less, per 100 parts by mass of the artificial nail composition. Although the hydrophilic compound is expected to have a certain effect in suppressing the clouding of the cured product over time, a high ratio of the hydrophilic compound may affect the strength of the cured product. In addition, a high ratio of the hydrophilic compound may cause problems due to the absorption of moisture from the natural nail.

[0039] In addition, in order to maintain a balance between the affinity and affinity of the (A) component, the lower limit of the content of the (meth)acrylate having a hydroxyl group is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 10 parts by mass or more, per 100 parts by mass of the artificial nail composition.

[0040] The content of the (A) component is not particularly limited, but when the artificial nail composition is used as a gel nail composition, that is, for coating (gel nail as a top gel layer applied to the surface side for polishing and protection), adhesion (gel nail as a base gel layer applied to the nail side to ensure adhesion to the nail), coloring (gel nail as a color layer for color development between the top gel layer and the base gel layer), etc., the lower limit of the content of the (A) component is preferably 0.5 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 30 parts by mass or more, and particularly preferably 50 parts by mass or more, relative to 100 parts by mass of the artificial nail composition. The upper limit of the content of the (A) component is preferably 90 parts by mass or less, more preferably 70 parts by mass or less, relative to 100 parts by mass of the artificial nail composition.

[0041] When the artificial nail composition is used as a primer (a liquid agent applied to the surface of the nail to improve adhesion between the nail and the gel nail; also called a nail primer or a base agent for gel nails), the lower limit of the content of component (A) is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 2 parts by mass or more, per 100 parts by mass of the artificial nail composition. The upper limit of the content of component (A) is preferably 40 parts by mass or less, more preferably 20 parts by mass or less, even more preferably 10 parts by mass or less, and especially preferably 8 parts by mass or less, per 100 parts by mass of the artificial nail composition.

[0042] [Component (B): an acidic phosphorus compound having at least one radically polymerizable unsaturated double bond in the molecule] In this embodiment, the component (B) includes one or more selected from hydroxybutyl (meth)acrylate acid phosphate, hydroxypentyl (meth)acrylate acid phosphate, and hydroxyhexyl (meth)acrylate acid phosphate.

[0043] According to the present embodiment, it is possible to obtain both high adhesive strength obtained from the polymerization reaction of the (meth)acrylic compound by component (A) and high adhesion to a substrate obtained by the acidic phosphorus compound by component (B), thereby obtaining good adhesion between a natural nail and an artificial nail.

[0044] In addition, since component (B) is a (meth)acrylic acid compound in which the groups constituting the polymerized units include one or more selected from butyl, pentyl, and hexyl groups, it has a lower Tg than (meth)acrylic acid compounds in which the groups constituting the polymerized units include methyl, ethyl, or propyl groups. The lower Tg makes the artificial nail composition more flexible and highly swellable in organic solvents when removing the cured product. This makes it easier to remove the artificial nail composition from the natural nail using an organic solvent according to the present invention.

[0045] Therefore, according to this embodiment, an artificial nail composition can be provided that achieves both good adhesion between a natural nail and an artificial nail and easy removability when removing the artificial nail from the nail plate of the natural nail.

[0046] The phosphate group-containing polymerizable monomer used in the artificial nail composition has a structure in which a spacer group is present between the hydrophilic phosphate group and the hydrophobic polymerizable group. The hydrophilicity of the entire phosphate group-containing polymerizable monomer changes depending on the structure of the spacer group, which is a factor that determines the compatibility with the main component of the artificial nail composition.

[0047] If the chain length of the spacer group is insufficient, the balance of the affinity and phosphatability of the entire phosphate group-containing polymerizable monomer will be biased toward hydrophilicity, and when the artificial nail composition is placed in a high temperature or humid environment, the phosphate group-containing polymerizable monomer will separate, affecting adhesion and curing properties. If the chain length of the spacer group is too long, the balance of the affinity and phosphatability of the entire phosphate group-containing polymerizable monomer will be biased toward hydrophobicity, and when the artificial nail composition is placed in a high temperature or humid environment, the adhesive function of the hydrophilic phosphate group will be significantly reduced, affecting adhesion. The present invention focuses on adhesion, which is the greatest point of market demand, and has found that a significant effect is achieved when the chain length of the spacer group is within the range of C4 (number of carbon atoms: 4) to C6 (number of carbon atoms: 6).

[0048] The content of the (B) component is not particularly limited, but when the artificial nail composition is used for the above-mentioned coating, adhesion, coloring, etc., the lower limit of the content of the (B) component is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the artificial nail composition. The upper limit of the content of the (B) component is preferably 40 parts by mass or less, more preferably 20 parts by mass or less, even more preferably 10 parts by mass or less, and particularly preferably 8 parts by mass or less, relative to 100 parts by mass of the artificial nail composition.

[0049] When the artificial nail composition is used as the above-mentioned primer, the lower limit of the content of the component (B) is preferably 0.5 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 30 parts by mass or more, and particularly preferably 50 parts by mass or more, per 100 parts by mass of the artificial nail composition. The upper limit of the content of the component (B) is preferably 90 parts by mass or less, more preferably 70 parts by mass or less, per 100 parts by mass of the artificial nail composition.

[0050] The component (B) may be a mixture of two or more types, rather than one type. Furthermore, the component (B) may contain a compound in which the chain length of the spacer group is C3 (number of carbon atoms: 3) or less and / or C7 (number of carbon atoms: 7) or more, as long as it does not affect quality deterioration after being placed in a high temperature or high humidity environment.

[0051] [Component (C): Radical Polymerization Initiator] The artificial nail composition according to the present embodiment contains a radical polymerization initiator. The use of a cationic polymerization initiator is not preferred because it may cause toxicity problems.

[0052] The radical polymerization initiator may be photocurable or heat curable, but since the artificial nail composition can be hardened within a period of tens of seconds to a few minutes, it is preferable that the radical polymerization initiator is photocurable.

[0053] [Photoradical polymerization initiator] When the artificial nail composition is photocurable, the component (C) is not particularly limited as long as it has the ability to initiate radical copolymerization by the action of light.For example, 4-phenoxydichloroacetophenone, 4-t-butyl-dichloroacetophenone, 4-t-butyl-trichloroacetophenone, diethoxyacetophenone, 2-hydroxy-2-phenyl-1-phenylpropan-1-one, 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 4-(2-hydroxyethoxy)-phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexylphenone, acetophenone-based initiators such as 1-[4-(methylthio)phenyl]-2-morpholinopropane-1, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1, etc.; benzoin-based initiators such as benzoin, benzoin methyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and benzyl methyl ketal; benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3'-dimethyl-4-methoxybenzyl benzophenone-based initiators such as benzophenone, 4,4'-dimethylaminobenzophenone, 4,4'-diethylaminobenzophenone, and 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone; thioxanthone-based initiators such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, isopropylthioxanthone, 1-chloro-4-propoxythioxanthone, and 2,4-dichlorothioxanthone; Initiators include ketone-based initiators such as α-acyloxime ester, methylphenyl glyoxylate, benzil, 9,10-phenanthrenequinone, camphorquinone, dibenzosuberone, 2-ethylanthraquinone, and 4',4''-diethylisophthalophenone; imidazole-based initiators such as 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-imidazole; acylphosphine oxide-based initiators such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide; and carbazole-based initiators.

[0054] The photoradical polymerization initiators may be used alone or in combination of two or more.

[0055] The content of the photoradical polymerization initiator is not particularly limited, but is preferably from 0.01 to 20 parts by mass, and more preferably from 0.1 to 10 parts by mass, per 100 parts by mass of the artificial nail composition.

[0056] [Thermal radical polymerization initiator] When the artificial nail composition is thermosetting, it is preferable that component (C) is thermosetting at room temperature.

[0057] As the thermal radical polymerization initiator having room temperature thermosetting properties, either an organic peroxide or an azo compound may be used. Specific examples of the organic peroxide include methyl ethyl ketone peroxide, cyclohexanone peroxide, methylcyclohexanone peroxide, methyl acetate peroxide, acetyl acetate peroxide, 1,1-bis(t-butylperoxy)butane, 1,1-bis(t-butylperoxy)-cyclohexane, 1,1-bis(t-butylperoxy)-2-methylcyclohexane, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)-4,4-dimethylphenylsilane, 1,1-bis(t-butylperoxy)-1,1-bis(t-butylperoxy)-2,4-dimethylphenylsilane, 1,1-bis(t-butylperoxy)- ... 1,1-bis(t-hexylperoxy)cyclododecane, 1,1-bis(t-hexylperoxy)-cyclohexane, 1,1-bis(t-hexylperoxy)-3,3.5-trimethylcyclohexane, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, t-butyl hydroperoxide, t-hexyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, p-menthane hydroperoxide, diisopropylbenzene hydroperoxide , di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, α,α'-bis(t-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3, isobutyryl peroxide, 3,3,5-trimethylhexanoyl peroxide, octanoyl peroxide, lauroyl peroxide, stearoyl peroxide, succinic acid peroxide , m-toluoyl benzoyl peroxide, benzoyl peroxide, di-n-propyl peroxydicarbonate, diisopropyl peroxydicarbonate, bis(4-t-butylcyclohexyl) peroxydicarbonate, di-2-ethoxyethyl peroxydicarbonate, di-2-ethoxyhexyl peroxydicarbonate, di-3-methoxybutyl peroxydicarbonate, di-s-butyl peroxydicarbonate, di(3-methyl-3-methoxybutyl) peroxydicarbonate, α,α'-Bis(neodecanoylperoxy)diisopropylbenzene, t-butyl peroxyneodecanoate, t-hexyl peroxyneodecanoate, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, 1-cyclohexyl-1-methylethyl peroxyneodecanoate, cumyl peroxyneodecanoate, t-butyl peroxypivalate, t-hexyl peroxypivalate, t-butyl peroxy- 2-Ethylhexanoate, t-hexylperoxy-2-ethylhexanoate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexanoate, 1-cyclohexyl-1-methylethylperoxy-2-ethylhexanoate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxyiso Propyl monocarbonate, t-hexylperoxyisopropyl monocarbonate, t-butylperoxy-2-ethylhexyl monocarbonate, t-butylperoxyallyl monocarbonate, t-butylperoxyisobutyrate, t-butylperoxymalate, t-butylperoxybenzoate, t-hexylperoxybenzoate, t-butylperoxy-m-toluylbenzoate, t-butylperoxylaurate, t-butylperoxyacetate, bis(t-butylperoxy)isophthalate, 2,5-dimethyl-2,5-bis(m-toluylperoxy)hexane, 2,5-dimethyl-2,5-bis(benzoylperoxy)hexane, t-butyltrimethylsilyl peroxide, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, 2,3-dimethyl-2,3-diphenylbutane, and the like.

[0058] Specific examples of azo compounds include 1-[(1-cyano-1-methylethyl)azo]formamide, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile, 2,2'-azobis(2-methylpropionamidine)dihydrochloride, 2,2-azo Bis(2-methyl-N-phenylpropionamidine) dihydrochloride, 2,2'-azobis[N-(4-chlorophenyl)-2-methylpropionamidine] dihydrochloride, 2,2'-azobis[N-(4-hydrophenyl)-2-methylpropionamidine] dihydrochloride, 2,2'-azobis[2-methyl-N-(2-propenyl)propionamidine] dihydrochloride, 2,2'-azobis[N-(2-hydroxyethyl)-2-methylpropionamidine] dihydrochloride, 2,2'-azobis[2-methyl-N-(phenyl 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl]propane}dihydrochloride, 2,2'-azobis[2-(4,5,6,7-tetrahydro-1H-1,3-diazepin-2-yl)propane}dihydrochloride pan]dihydrochloride, 2,2'-azobis[2-(3,4,5,6-tetrahydropyrimidin-2-yl)propane]dihydrochloride, 2,2'-azobis[2-(5-hydroxy-3,4,5,6-tetrahydropyrimidin-2-yl)propane]dihydrochloride, 2,2'-azobis(2-methylpropionamide), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,Examples of the azobis(2-methyl-N-[1,1-bis(hydroxymethyl)ethyl]propionamide) include 2,2'-azobis(2-methylpropane), 2,2'-azobis(2,4,4-trimethylpentane), dimethyl 2,2-azobis(2-methylpropionate), 4,4'-azobis(4-cyanopentanoic acid), and 2,2'-azobis[2-(hydroxymethyl)propionitrile].

[0059] The thermal radical polymerization initiators may be used alone or in combination of two or more.

[0060] The content of the thermal radical polymerization initiator is not particularly limited, but is preferably from 0.01 to 10 parts by mass, and more preferably from 0.1 to 5 parts by mass, per 100 parts by mass of the artificial nail composition.

[0061] The component (C) may contain both a thermal radical polymerization initiator and a photoradical polymerization initiator.

[0062] [Various additives] The artificial nail composition of the present embodiment may contain various known additives as necessary. Examples of such additives include polymerization accelerators, polymerization inhibitors, colorants, discoloration inhibitors, fluorescent agents, ultraviolet absorbers, antibacterial agents, volatile organic solvents, etc. EXAMPLES

[0063] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. There is none.

[0064] <Artificial nail composition> [Ingredients used] (A) A radically polymerizable compound having one or more radically polymerizable unsaturated bonds in one molecule [Hydrophobic polymerizable monomer] AH1: bisHEA (poly(1,4-butanediol)-9 / IPDI) copolymer AH2: Isobornyl methacrylate [Hydrophilic polymerizable monomer] AP1: 2-hydroxyethyl methacrylate AP2: 2-hydroxypropyl methacrylate

[0065] (B) Phosphate ester compound B1: 2-Hydroxyethyl acrylate acid phosphate (comparative example) B2: 2-Hydroxypropyl acrylate acid phosphate (comparative example) B3: 4-Hydroxybutyl acrylate acid phosphate (Example) B4: 6-hydroxyhexyl methacrylate acid phosphate (Example)

[0066] (C) Photopolymerization initiator C1: 2,4,6-trimethylbenzoyldiphenylphosphine oxide

[0067] [Preparation of Artificial Nail Composition] According to the adjusted mixture in Tables 1 and 2, the above-mentioned components A1-A4, B1-B5, and C1 were weighed out using an electronic balance, and then stirred and mixed to prepare the artificial nail compositions of Examples 1-9 and Comparative Examples 1-9. [Table 1] [Table 2]

[0068] <Evaluation test> Each of the prepared artificial nail compositions was subjected to a stability evaluation, an adhesion test, and a removability test according to the procedures described below.

[0069] [Evaluation test procedure] [Evaluation of stability in high temperature environments] The compatibility of the phosphate group-containing polymerizable monomer in the artificial nail composition was evaluated. (Stability evaluation and evaluation scale) 20 g of the prepared artificial nail composition was filled into a transparent glass container (volume: 30 ml) and left to stand for 7 days in a light-shielded environment at 50°C. After leaving to stand for 7 days, the state of the contents was visually confirmed. If the components were mixed uniformly and no precipitation, aggregation, or precipitate was observed in the contents, the composition was deemed to have good stability as an artificial nail composition, and if precipitation, aggregation, or precipitate was observed in the contents, the composition was deemed to be unsuitable as an artificial nail composition.

[0070] [Evaluation of stability under high temperature and humidity conditions] 20g of the prepared artificial nail composition was filled into a transparent glass container (volume: 30ml) and kept in a light-shielded state. However, the container was not sealed, but the cap was removed and the top was left open, and it was left to stand for 15 hours in an environment of 40℃ and 100% relative humidity (RH). After standing, the condition of the contents was visually confirmed. If the components were mixed uniformly and the contents showed no precipitation, aggregation, or deposits, or color changes due to moisture absorption, it was determined to have good stability as an artificial nail composition, and if the contents showed precipitation, aggregation, or deposits, or color changes due to moisture absorption, it was determined to be unsuitable as an artificial nail composition.

[0071] [Adhesion test] In the adhesiveness test, the artificial nail composition was applied to the natural nail of a subject, cured, and then the adhesiveness of the artificial nail composition was evaluated after a certain period of daily life. The detailed procedure of the adhesiveness test is shown below.

[0072] (Preparation of samples for adhesion test) Use a nail file for gel nails (nail file, grit size: 600) to file the natural nail surface to obtain a fresh surface.

[0073] Next, the fresh surface is wiped with an ethanol-soaked wipe to remove dust and oil.

[0074] Next, an artificial nail composition is applied to the fresh surface from which dust and other particles have been removed, and then cured using a commercially available LED light specifically for gel nails.

[0075] Next, a commercially available top gel is applied on top of the hardened artificial nail composition and hardened using a commercially available LED light for gel nails. The top gel is a gel nail material that is applied to the surface of the gel nail beauty product, such as the artificial nail composition, applied to the natural nail to obtain a good shine. (Adhesion evaluation and evaluation scale in adhesion test) The subjects carried out their daily lives for 14 days with the cosmetics applied to their natural nails. The condition of the cured artificial nail composition on the natural nail after the 14-day period was classified according to the scale in Table 3 and used as the evaluation score for the adhesion test. [Table 3]

[0076] [Removability test] In the removability test, the artificial nail composition was applied to the natural nail of the subject, cured, and then the subject was allowed to live a normal life for a certain period of time, after which the removability of the artificial nail composition was evaluated, as in Adhesion Test 2. The detailed procedure for the removability test is shown below.

[0077] (Preparation of samples for removability test) The preparation of the sample for the removability test was similar to that for the adhesion test.

[0078] (Evaluation and evaluation scale of removability in removability test) The subject goes about his or her daily life for 14 days with the cosmetic product prepared for the removability test applied to their natural nails.

[0079] For cosmetic applications such as the hardened artificial nail composition on the natural nail after 14 days of daily life, the top gel on the outermost surface is scraped off using a nail file for gel nails (nail file, coarseness: 80 grit).

[0080] Then, a wipe soaked in acetone is placed on the artificial nail composition hardened body from which the top gel has been scraped off, and the fingertip is wrapped in aluminum foil. This prevents the acetone from evaporating, and the artificial nail composition hardened body becomes swollen by the acetone. The fingertip is left to stand for 10 minutes, after which the aluminum foil and wipe are removed.

[0081] After removing the aluminum foil and wipe, an attempt was made to remove the hardened artificial nail composition from the natural nail, and the state of removal was observed. The results of this observation were classified according to the scale in Table 4, and this was used as the evaluation score (removability) of the removability test. [Table 4]

[0082] [Evaluation test results] The results of the evaluation test are shown in Tables 5 and 6. [Table 5] [Table 6]

[0083] [Stability] The artificial nail compositions of Examples 1 to 9 all had excellent stability, and no precipitation, aggregation, or deposits were observed in the contents even after being left to stand for 7 days in an environment at 50° C. Even after being left to stand for 15 hours in an environment at 40° C. and 100% RH, the uniformity of each component was maintained and no change in the contents was observed, although the surface became slightly cloudy due to moisture absorption.

[0084] In contrast, in the artificial nail compositions of Comparative Examples 1 to 9, the phosphate ester compound, which is the component (B), separated and settled on the bottom of the container. In particular, when left to stand for 15 hours in a 40°C, 100% RH environment, the surface became significantly cloudy due to moisture absorption, and a clear change in color tone was observed. The (meth)acrylate group exhibits hydrophobicity, and the phosphate group exhibits hydrophilicity. In general, the phosphate group-containing polymerizable monomer used in the artificial nail composition has a structure in which a spacer group exists between the hydrophilic phosphate group and the hydrophobic polymerizable group. The butyl and hexyl groups, which are the spacer groups in the examples, have more carbon atoms and are more hydrophobic than the ethyl and propyl groups, which are the spacer groups in the comparative examples, so that the compounds B3 and B4 in the examples are biased toward hydrophobicity as a whole compared to the compounds B1 and B2 in the comparative examples. Therefore, it is considered that the compatibility with the component (A), which is the main component of the artificial nail composition, is good, and the separation of the component (B) over time does not occur even after being placed in a high temperature environment or a high temperature and high humidity environment. Furthermore, it was expected that an increase in the hydrophobicity of component (B) would cause component (B) itself to not function as an acidic compound, resulting in a decrease in adhesiveness; however, adhesion tests confirmed that the compound had good adhesiveness.

[0085] On the other hand, in the artificial nail compositions of Comparative Examples 1 to 9, the chain length of the spacer group was insufficient, and the balance of the phosphate group-containing polymerizable monomer as a whole was too biased toward hydrophilicity, which is thought to have caused the phosphate group-containing polymerizable monomer to separate.

[0086] [Adhesiveness] In Examples 1 to 9, both the samples immediately after preparation of the artificial nail composition and the samples left standing for 7 days in a 50°C environment showed good adhesion. In contrast, in Comparative Examples 1 to 9, the samples immediately after preparation showed good adhesion, but the samples left standing for 7 days in a 50°C environment did not show sufficient adhesion. This is presumably because the balance between the high adhesive strength obtained from the polymerization reaction of the (meth)acrylic compound by component (A) and the high adhesion to the substrate obtained by the acidic phosphorus compound by component (B) was lost, and sufficient adhesion to the substrate was not obtained at the adhesive interface.

[0087] [Removability] The artificial nail compositions of Examples 1 to 9 had good removability from the nail plate surface as cured products, and could be removed without damaging the nail plate surface. In contrast, the artificial nail compositions of Comparative Examples 1 to 9 peeled off and fell off from the natural nail within 14 days, so removability could not be evaluated. [Industrial Applicability]

[0088] According to the invention described in this embodiment, an artificial nail composition can be provided that suppresses hydrolysis of compounds such as urethane acrylate and (meth)acrylate monomers caused by exposure to a high temperature or high humidity environment, particularly deterioration of the phosphate group-containing polymerizable monomer caused by loss of the compatibility balance of the phosphate group-containing polymerizable monomer, thereby providing an artificial nail composition that can be stably applied even in the hot and humid summer season.

Claims

1. (A) a compound having at least one radically polymerizable unsaturated double bond in the molecule and having no phosphorus atom; (B) an acidic phosphorus compound having at least one radically polymerizable unsaturated double bond in the molecule; (C) a radical polymerization initiator, The component (B) includes at least one selected from hydroxybutyl (meth)acrylate acid phosphate, hydroxypentyl (meth)acrylate acid phosphate, and hydroxyhexyl (meth)acrylate acid phosphate. Artificial nail composition.

2. 2. The artificial nail composition according to claim 1, wherein the component (A) comprises a (meth)acrylate having no hydroxyl group and a (meth)acrylate having a hydroxyl group.

3. The artificial nail composition according to claim 2 , wherein the (meth)acrylate having a hydroxyl group includes hydroxyethyl (meth)acrylate and / or hydroxypropyl (meth)acrylate.

4. 4. The artificial nail composition according to claim 2, wherein the content of the (meth)acrylate having a hydroxyl group is 35 parts by mass or less per 100 parts by mass of the artificial nail composition.

Citation Information

Patent Citations

  • Raw material composition for artificial nails, curing method of raw material composition for artificial nails, production method for artificial nails, and artificial nails

    JP2015209375A

  • Base coat composition for nail art

    JP2018080129A

  • Artificial claw components

    JP7104392B1